Exploration of Youtuber Business Models as an Additional Reference for Current Professional Opportunities - Deni Asmayadi (Publikasi Indonesia, 2024)
This research explores the opportunities for YouTubers' digital workers today. The existence of opportunities to earn income from the YouTube platform in the form of AdSense, as well as other income opportunities that are open because of being a YouTuber makes people want to engage in this digital worker. Either as a side job or as a main job. No research explores the current YouTuber business model, making this research important to be used as an additional reference for those who want to become YouTubers. This research applies a qualitative method whose goal is to explore information in depth. With in-depth interviews with 2 big YouTubers and 2 beginner YouTubers as well as Employees of the Directorate General of Taxes, the author found that currently, the work of YouTubers is not as prospective as it used to be, because the competition between YouTubers is very tight, and the regulations imposed by YouTube related to AdSense are also felt by informants. In conclusion, to start a career as a content creator on YouTube, and then make it your main income for now seems less recommended. Apart from the fact that there are many YouTubers, it means that the red ocean or competition is saturated, also the adsense received turns out to be